2019
DOI: 10.3390/met9060639
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Influences of Prior Residual Stress on the Creep Rupture Mechanism for P92 Steel

Abstract: Creep damage is one of the main failure mechanisms of high Cr heat-resistant steel in power plants. Due to the complex changes of stress, strain, and damage at the tip of a creep crack with time, it is difficult to accurately evaluate the effects of residual stress on the creep rupture mechanism. In this study, two levels of residual stress were introduced in P92 high Cr alloy specimens using the local out-of-plane compression approach. The specimens were then subjected to thermal exposure at the temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Creep damage evolution can also be carefully modelled by innovative combinations of experimental investigation techniques, such as small-angle neutron scattering (SANS), scanning electron microscopy, and quantitative metallography, as reported by Jazeri et al in [4] in the case of a 304 stainless steel. The effects of prior residual stress left by welding processes on the damage at the crack tip of a 9-12% Cr steel specimen with simulated weldment was investigated experimentally by Liu et al [5], who observed residual stress-related transition of damage forms.…”
Section: Creep Deformation Damage and Ductilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Creep damage evolution can also be carefully modelled by innovative combinations of experimental investigation techniques, such as small-angle neutron scattering (SANS), scanning electron microscopy, and quantitative metallography, as reported by Jazeri et al in [4] in the case of a 304 stainless steel. The effects of prior residual stress left by welding processes on the damage at the crack tip of a 9-12% Cr steel specimen with simulated weldment was investigated experimentally by Liu et al [5], who observed residual stress-related transition of damage forms.…”
Section: Creep Deformation Damage and Ductilitymentioning
confidence: 99%
“…The paper by Wu et al [11] deals with the effect of heat treatment process parameters, and specifically the normalizing temperature, in grade 91, a 9-12% Cr steel, which is discussed on the basis of a careful microstructural analysis of crept samples. Other critical features for the industrial applications of these steels have been considered in the Issue, such as weld joint behaviour (Hu et al [5] investigated the effect of residual stresses left by these processes on creep damage) or creep-fatigue and creep relaxation phenomena (Jürgens et al [10]).…”
Section: Creep-microstructure Correlations For Specific Materials Classesmentioning
confidence: 99%